PENGELOLAAN SAMPAH PLASTIK MENJADI ECOBRICK UNTUK MENEKAN LAJU PENCEMARAN MIKROPLASTIK DI KELURAHAN KAMPUANG JUA KECAMATAN LUBUK BEGALUNG KOTA PADANG - Deswati Deswati; Buty Kurnia Hamzani; Olly Norita Tetra (LPPM Universitas Andalas, 2023)
As people's consumption levels increase, the plastic waste produced increases, so that plastic waste becomes the first environmental problem in Indonesia, especially in Kelurahan Kampung Jua Nan XX, Kecamatan Lubuk Begalung, Padang City. Plastic waste takes a long time to disintegrate and can decompose into microplastics which can be spread into soil and water. The presence of microplastics in soil and water can contaminate plants, shellfish, fish and even salt which ultimately accumulates in the human body through the food chain cycle. Therefore, a solution is needed so that the presence of plastic waste can be handled properly and carried out optimal management. One solution to utilizing plastic waste is by making ecobrick products that are useful and have high selling value and can be a livelihood opportunity. The aim of this activity is to increase public awareness and concern for the environment in order to create a clean and healthy environment through the management and processing of plastic waste. This activity was carried out in kelurahan Kampung Jua on 27 October and 9 December 2022, with the participants in this activity being PKK women from Kampung Jua Nan XX Village. The methods used were education regarding the threat of plastic and microplastic waste and training through demonstrations on making chairs from ecobricks. The results of this activity can increase public awareness of the dangers of plastic waste, limit the use of plastic bags and manage plastic waste at the source as an effort to reduce plastic waste generation and empower the community to maximizing the economic value of existing waste in a sustainable manner.